Bowel Obstruction: Decompressive Gastrostomies and Cecostomies - Miller, Zoe A.; Mohan, Prasoon; Tartaglione, Robert; Narayanan, Govindarajan (Seminars in Interventional Radiology, 2017)
Over the past 30 years, image-guided placement of gastrostomies and cecostomies for gastrointestinal decompression has developed into a safe and effective treatment for symptomatic bowel obstruction. Gastrostomies and cecostomies relieve patient symptoms, can prevent serious complications such as colonic perforation, and may bridge patients to more definitive treatment for the underlying cause of obstruction. This article will review the history of decompressive gastrostomies and cecostomies as well as the indications, contraindications, technique, complications, and outcomes of these procedures.
Keywords: palliative care; gastrostomy; cecostomy; bowel obstruction; interventional radiology